O efeito da propaganda no comportamento de escolha de bebidas das crianças - (:unkn) unknown (Universidade Federal de Goiás, 2017)
The research in the area of study of consumer behavior is related to the multidisciplinarity of this area, when you speak of food consumption, several studies seek to analyze the influence of advertising on the food choice of people. Analysis has also been realized in order to check the children’s preference as consumers of food and beverages. Within the behavioral perspective studies have been carried out using the Foxall model of the BPM (Behavior Perspective Model) seeking to understand consumer behavior by the threefold contingency from the analysis of its elements: antecedent, response and consequent. This paper aims to evaluate the effects of advertising exposure on the choice of children for beverages, as well as the effect of the number of alternatives available during the choice through the use of the BPM model. An experiment was carried out with 16 children of both sexes, aged between 10 and 12 years old, using a board game and presenting drinks advertisements: juice, soda and a toy advertisement. The participants were divided into four groups; for each group, one of the advertisements was presented before the beginning of the game, when they had to make the choice between juice or soda during 20 trials in each session, and two sessions were held. The results showed that the advertisements had no influence on the participants' choices, because, regardless of the advertisement, the children showed a preference for juice instead of the refrigerant. The number of alternative choices presented in format for group four seems to have exerted influence on the choices during the trials.
Keywords: Comportamento do consumidor; Preferência de escolha; BPM (behavior perspective model); Escolha alimentar de crianças; Consumer behavior; Choice preference; BPM (behavior perspective model); Choose child feeding; ADMINISTRACAO DE EMPRESAS::ADMINISTRACAO DE RECURSOS HUMANOS